Volatile components, antibacterial and antioxidant activities of komburongoh (Acorus Calamus L.) essential oils as potential medicinal herbs from Sabah, Malaysia - Mohammad Amil Zulhilmi Benjamin; Jacqueline Vincent; Haja Nursadah Binsali; Ahmad Asnawi Mus; Mohd Azrie Awang; Nor Azizun Rusdi (UNIMAS Publisher, 2025)
Acorus calamus L., known for diverse therapeutic applications, was studied for its volatile components, antibacterial and antioxidant potential in essential oils from Sabah, Malaysia. Employing hydrodistillation with a Clevenger apparatus, the oils were analysed through gas chromatography-mass spectrometry. Antibacterial activity was assessed via disc diffusion against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli. Antioxidant properties were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. Both leaf and rhizome oils were rich in phenylpropanoids, oxygenated sesquiterpenes, and sesquiterpenes including α-asarone, γ-asarone, methyl isoeugenol, 6-epishyobunone, and (E)-β-farnesene. They demonstrated significant antibacterial activity at 400 µg/mL, while displaying lower DPPH (IC50 = 28.20 ± 4.99 µg/mL) and excelling in the FRAP (150.12 ± 0.10 mg TE/g). This ongoing phytochemical analysis of A. calamus holds promise for enhancing quality control, ensuring safety, and validating its traditional applications.